The no-nonsense guide to project management - Allan, Barbara, 1954- (Facet Publishing, 2017)
This book provides a 'no-nonsense' guide to project management which will enable library and information professionals to lead or take part in a wide range of projects from large-scale multi-organisation complex projects through to relatively simple local ones.